Membangun Kesadaran Sosial Melalui Kegiatan Pengajaran Dasar – Dasar Kehidupan Sosial Pada Mahasiswa Universitas Sunan Giri Surabaya - Nunik Hidayati; Rekha Widiawati; Zhunnun Qothrunnada Annisa Salam Al-Madury; Farida Nabilah; Rahayu Mardikaningsih; Fayola Issalillah; Eli Masnawati; Asnal Mala; Masfufah Masfufah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Teaching activities are a mechanism of community service activities containing many positive impacts for students, one of which is increasing a sense of caring, mutual respect, and fostering critical thinking in dealing with social problems that are developing today. This student teaching service activity uses the PAR (Participatory Action Research) method which is an approach that overcomes problems that occur in students' lives, especially in their social lives. In the context of this activity, namely building students' social awareness through teaching activities using the PAR method, it can enable students to learn a lot of new knowledge about social issues and they can even participate directly in social activities that are developing in people's lives today. This PAR method is carried out through several series, namely first identifying problems that occur in the lives of students today and looking for real examples of social problems related to the environment around them. After that, collecting data which includes material that will be delivered to students, and for the last stage, namely the implementation stage by presenting the material, the implementation of actions designed in the use of the PAR method directly involves third semester students of Sunan Giri University Surabaya. The results showed that student teaching activities succeeded in increasing understanding and social awareness in students, because in lecture activities students are always directly involved in a learning activity which discusses the introduction of important concepts from the basics of social life.